Adapting the cosmological tradition in Isaiah 40-45 - Crouch, C.L. (Taylor & Francis, 2011)
The characterisation of Yahweh as king in Isaiah 40-45 and the use of creation language to reiterate Yahweh's power are well known. This article examines the way in which these themes reflect this text's re-working of pre-exilic theology in order to cope with the exilic situation. It discusses the pre-exilic military tradition, especially in relation to Yahweh's roles as warrior, king and creator, then examines how Isaiah 40-45 adapts this tradition to a changed reality. It concludes that the author has abandoned the traditional rendering of the Chaoskampf, in which Yahweh's roles as warrior, king and creator are linked, in order to retain the characteristics necessary to persuade the exiles of Yahweh's power to save. Though Yahweh remains warrior, king and creator, these characteristics are no longer interconnected.